2006
DOI: 10.1183/09031936.06.00058505
|View full text |Cite
|
Sign up to set email alerts
|

Carbocisteine inhibits rhinovirus infection in human tracheal epithelial cells

Abstract: The aim of the study was to examine the effects of a mucolytic drug, carbocisteine, on rhinovirus (RV) infection in the airways.Human tracheal epithelial cells were infected with a major-group RV, RV14. RV14 infection increased virus titres and the cytokine content of supernatants. Carbocisteine reduced supernatant virus titres, the amount of RV14 RNA in cells, cell susceptibility to RV infection and supernatant cytokine concentrations, including interleukin (IL)-6 and IL-8, after RV14 infection. Carbocisteine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
46
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 29 publications
7
46
0
1
Order By: Relevance
“…COPD patients treated with carbocysteine experienced fewer numbers of exacerbations per year (Zheng et al 2008). This effect may be linked to the reduced adherence of bacterial pathogens to airway epithelial cells (Rahman and Macnee 2012) and to the downregulation of ICAM-1, a receptor for the major group of rhinovirus (Yasuda et al 2006). Moreover, carbocysteine inhibiting cell apoptosis and promoting the reversal of the imbalance of proteolytic and anti-proteolytic enzyme activities protects against the development of CSEinduced emphysema in rats (Hanaoka et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…COPD patients treated with carbocysteine experienced fewer numbers of exacerbations per year (Zheng et al 2008). This effect may be linked to the reduced adherence of bacterial pathogens to airway epithelial cells (Rahman and Macnee 2012) and to the downregulation of ICAM-1, a receptor for the major group of rhinovirus (Yasuda et al 2006). Moreover, carbocysteine inhibiting cell apoptosis and promoting the reversal of the imbalance of proteolytic and anti-proteolytic enzyme activities protects against the development of CSEinduced emphysema in rats (Hanaoka et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In rhinovirus infections, S-CMC reduces expression of the receptor intercellular adhesion molecule-1 (ICAM-1) and production of cytokines in human tracheal epithelial cells (Yasuda et al, 2006). Additionally, S-CMC reduces the concentration of IL-6 in the breath condensate of acute COPD patients (Carpagnano et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Despite the increase in bacterial adherence to the cells, S-CMC efficiently reduced the enhanced adherence of both strains to the epithelial cells in a dose-dependent manner. These results suggest that the potency of S-CMC against S. pneumoniae adherence contributes to a reduction in COPD symptom exacerbation.In rhinovirus infections, S-CMC reduces expression of the receptor intercellular adhesion molecule-1 (ICAM-1) and production of cytokines in human tracheal epithelial cells (Yasuda et al, 2006). Additionally, S-CMC reduces the concentration of IL-6 in the breath condensate of acute COPD patients (Carpagnano et al, 2004).…”
mentioning
confidence: 99%
“…Carbocysteine may also modulate airway inflammation by reducing the production of cytokines in rhinovirus infections [31]. It has also been shown that carbocysteine inhibits the adherence of bacteria and viruses to ciliated epithelial cells in vitro [31,32].…”
Section: Mucoregulatorsmentioning
confidence: 99%